2016
DOI: 10.1016/j.jclepro.2016.06.132
|View full text |Cite
|
Sign up to set email alerts
|

The state of supply chain carbon footprinting: analysis of CDP disclosures by US firms

Abstract: Although collaboration and performance measurement are widely recognized as critical for increasing sustainability in supply chains, little is known about how comprehensively firms are currently measuring their supply chain carbon emissions (or Scope 3). We develop a way to assess how complete firms' reports of Scope 3 emissions are, by comparing them to benchmarks based on Environmental Input-Output Life-Cycle Assessment models. We use this approach to evaluate Scope 3 carbon emissions disclosed by many of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
69
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 87 publications
(78 citation statements)
references
References 36 publications
3
69
0
2
Order By: Relevance
“…Blanco et al argued that little is known about how comprehensively firms are currently measuring their supply chain carbon emissions-or upstream Scope 3 [10]. Innakollu et al concluded that one of the uncertainties in Scope 3 calculations arise from the amount of CO 2 -eq.…”
Section: Review Of Prior Knowledge Observationsmentioning
confidence: 99%
“…Blanco et al argued that little is known about how comprehensively firms are currently measuring their supply chain carbon emissions-or upstream Scope 3 [10]. Innakollu et al concluded that one of the uncertainties in Scope 3 calculations arise from the amount of CO 2 -eq.…”
Section: Review Of Prior Knowledge Observationsmentioning
confidence: 99%
“…Firms also engage in carbon footprinting as a way to identify opportunities for cost savings, given that carbon hotspots often point to opportunities for profitable energy efficiency initiatives. Matthews and colleagues () estimate that, on average, 74% of a firm's carbon footprint (CF) falls in its upstream supply chain, though Blanco and colleagues () estimate that U.S. firms that reported any scope 3 emissions at all as part of their CDP disclosures in 2013 only reported 22% of what would be expected based on Matthews and colleagues (). Given this variety of reasons to conduct an LCA or CF, there is a similar multitude of ways to do so.…”
Section: Short Histories Of Industrial Ecology and Sustainable Supplymentioning
confidence: 99%
“…Most of the CDP disclosures focus on Scope 1 and 2 emissions, which are expected to be reasonably complete; Scope 3 emissions (those elsewhere in the firm's supply chain) are entirely discretionary. Blanco et al (2016b) estimate that firms only disclose 22% of their Scope 3 emissions (if they disclose at all), and CDP itself believes that "current Scope 3 reporting does not reflect the full impact of companies' activities, and may mislead as to the full carbon impact of a company" (CDP 2014, p. 9). All in all, our findings suggest that the supply chain perspective is crucial for finding ongoing emissions reduction opportunities, but that both with respect to measurement and disclosure, firms are not yet taking as much of a supply-chain perspective as they should.…”
Section: Take a Supply Chain Perspectivementioning
confidence: 99%
“…Blanco et al (2016b) estimate that even the firms in the US who disclose some Scope 3 emissions to CDP on average only report 22% of the emissions that one would expect based on an external benchmark by Matthews et al (2008), suggesting that many such opportunities are currently going unrecognized. To exploit such opportunities would require collaborating with supply chain partners.…”
mentioning
confidence: 99%